Equity Ownership and Financial Performance - Srivastava, Aman (Journal of Economics and Behavioral Studies, 2011)
This paper attempts to examine the relationship of equity ownership and financial performance of firms in India. The study explored the possibility that whether equity ownership type affects the financial performance of listed Indian firms. The study examined the relationship of equity ownership with accounting as well as market measures of financial performance of the firms. The study sampled the 500 listed companies constituting BSE 500 indices of Bombay Stock Exchange of India. The 397 most actively listed companies on BSE 500 indices of Bombay Stock Exchange of India, which constitute the bulk of trading, were chosen to constitute the sample of the study as of end of 2009-10. The study used Ordinary least square (OLS) to examine the relationship between the equity ownership and financial performance of the Indian listed firms. The findings of the study depict the presence of highly concentrated ownership structure in the Indian market. The results of the regression analyses interestingly indicate that the dispersed equity ownership influences certain dimensions of accounting financial performance measures (i.e. ROA and ROE) but not market performance measures (i.e. Tobin’s Q, P/E and P/BV ratios), which indicate that there might be other factors (Behavioral, macro economic, political, contextual) affecting firms performance other than ownership structure. The findings of the study might be relevant for practitioners and investors for taking their financing and investment decisions.